Stylish and Sustainable: How Gen Z in Indonesia is Shaping the Future of Fashion - Aslam, Annisa Paramaswary; Putra , Muh Al Fatah Arief; Hardiyanti, Andi Aryani; Palangkey, Nurul Rahmi; Mushawwir , Shaleh Afief A (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to explore Generation Z’s perspectives on sustainable fashion consumption and the marketing strategies used within the Indonesian market. By analyzing their purchasing behavior, the research seeks to gain a deeper understanding of how this generation engages with and interprets sustainable fashion. This study examines Generation Z’s attitudes toward sustainable fashion consumption and marketing through a deductive qualitative approach, drawing on fashion business theory, consumer motivation, and sustainable consumption. Framing research questions as hypotheses, it tests existing theories using insights from 11 purposively selected Gen Z participants in Makassar who have studied abroad and engaged with sustainable products. This study identifies four key themes shaping Generation Z’s attitudes toward sustainable fashion: Design, Diversity, Desirability, and Digitalization. These reflect how Gen Z responds to external psychological, cultural, and social factors that influence their purchasing behavior.